Development and validation of a gas chromatography with a flame ionization detector method for quantitative analysis of four major fatty acids extracted shark liver oil - Pedro C. Quero-Jiménez; Lester A. Arias Felipe; María E. Jorge Rodríguez; Reinaldo Molina Ruiz; Julio O. Prieto García; Jorge B. de la Torre López; Osvaldo N. Montenegro (GarVal Editorial Ltda., 2021)
Context: The shark liver of the species Ginglimostoma cirratun, Carcharhinus longimanus, and Carcharhinus falciformis, captured in the north-central coast of Cuba are a source of oil, whose content of major fatty acids could be used in its quality control. Aims: To develop a simple and robust gas chromatography with a flame ionization detector (GC-FID) method that is suitable for routine analysis of four major fatty acids extracted shark liver oil. Methods: Four major fatty acid content in shark liver oil pool of species Ginglimostoma cirratun, Carcharhinus longimanus, and Carcharhinus falciformis, was analyzed through the gas chromatography with a GC-FID. The fatty acids were analyzed as methyl esters derivatives, using 5% aqueous sulfuric acid in methanol. The method was validated in terms of linearity, precision, accuracy, specificity and limit of detection and quantitation. Results: Under the optimum analytical conditions, the analysis revealed that each target component was well separated with satisfactory recoveries and reproducibility. The method linearity was found to be high with good determination coefficient values for all target components. The evaluation of the matrix effect, demonstrated, that there is not interference from substances other than analysis. The method was also found to be accurate, precise and reproducible and it was applied to the quantitative determination of the fatty acid content in shark liver oil pool; oleic acid was the most abundant fatty acid (22.69%), followed by palmitic (18.85%), stearic (6.01 %) and myristic acid (0.40 %). Conclusions: The GC-FID developed method is reliable and suitable for determination of four major fatty acids in shark liver oil pool.